ANALISIS FAKTOR PENYEBAB PELANGGARAN DISIPLIN SISWA DI SMK KANSAI PEKANBARU - Fajri, Hamidah; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the level of discipline violation by students of SMK KANSAI Pekanbaru is still quite high. So the authors take the title of research "Analysis of Factors Cause Student Discipline Violation in SMK KANSAI Pekanbaru". The formulation of the problem in this research is: What is the dominant factor and the reason students do violation of student discipline in SMK KANSAI Pekanbaru? The purpose of this study is to determine the dominant factors and reasons students do violations of student discipline in vocational KANSAI Pekanbaru. The population of this study were students of SMK KANSAI who committed violations amounted to 266 people and the sample amounted to 53 people. The questionnaire instrument consists of 31 questions. The interview consisted of 31 questions. In analyzing the data using Qualitative Descriptive analysis. The results of this study indicate that the dominant factor causing violation of student discipline is a factor of discipline violation arising by students with percentage of 76.73%. While the reason students do discipline violations are: students do strange to attract attention (86.79%) with the reason that the atmosphere looks more relaxed, students who lack reading (88.68%) on the grounds because students are lazy to read books, especially reading textbooks, students do not do the tasks of the teachers (88.68%) with the reason students are lazy to do their own work prefer to cheat the task of friends, and students who like to come to school without self-preparation (83.02%) on the grounds because at night they do not prepare what to bring to school.Keywords: Cause Violation, Discipline